Colletotrichum dracaenigenum, a new species on Dracaena fragrans - Chaiwan, Napalai; Tibpromma, Saowaluck; Jayawardena, Ruvishika S.; Mapook, Ausana; Wanasinghe, Dhanushka N.; Mortimer, Peter E.; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2021)
During an investigation into the microfungi on Dracaena fragrans in Thailand, a saprobic taxon belonging to Glomerellaceae was collected. Based on morphological characterization and combined phylogenetic analyses of ITS, GAPDH, CHS-1, ACT and TUB2 sequence data from the sexual and asexual morphs our taxon was identified as a new species of Colletotrichum. Colletotrichum dracaenigenum sp. nov. is introduced here with a full description, colour photographs of morphological characteristics and a phylogenetic tree to show the placement of the new taxon in the gloeosporioides species complex.